A line-feature label placement algorithm for interactive 3D map. (October 2017) - She, Jiangfeng; Liu, Jianlong; Li, Chuang; Li, Jiaqi; Wei, Qiujun
Highlights: A line-feature label placement algorithm for 3D interactive map is proposed. A view dependent annotation-referencing line is used to position the labels at different scale. Aggressive occlusion culling based on shadow map is performed on each label. Conflicts of labels are resolved in screen space. Graphical abstract: Abstract: In an interactive three-dimensional (3D) map, the relief of the terrain can obstruct annotations. As the perspective moves and rotates freely in 3D space, the occlusion relationship among annotations changes accordingly. The direction of a line in general definitively influences the orientations of the characters in its annotation label, which affects its readability. Furthermore, a line that extends deep into 3D space requires annotation-reference line segments at different scales because the distant parts of a line appear less detailed than closer ones, and the positioning of the text of its annotation should be adjusted accordingly. In this paper, a rule set for 3D interactive map line-feature annotations is proposed and a screen-based line-feature annotation-placement algorithm is implemented. The purpose of our algorithm is to ensure that the annotations are readable from multiple angles, not obstructed by other annotations, terrains, or artificial structures, convey the directions of the lines, and conform to the traditional positioning preferences in cartography.